Terebra steering in chalcidoid wasps - Benjamin Eggs; Stefan Fischer; Michael Csader; István Mikó; Alexander Rack; Oliver Betz (Frontiers in Zoology, 2023)
Abstract Various chalcidoid wasps can actively steer their terebra (= ovipositor shaft) in diverse directions, despite the lack of terebral intrinsic musculature. To investigate the mechanisms of these bending and rotational movements, we combined microscopical and microtomographical techniques, together with videography, to analyse the musculoskeletal ovipositor system of the ectoparasitoid pteromalid wasp Lariophagus distinguendus (Förster, 1841) and the employment of its terebra during oviposition. The ovipositor consists of three pairs of valvulae, two pairs of valvifers and the female T9 (9th abdominal tergum). The paired 1st and the 2nd valvulae are interlocked via the olistheter system, which allows the three parts to slide longitudinally relative to each other, and form the terebra. The various ovipositor movements are actuated by a set of nine paired muscles, three of which (i.e. 1st valvifer-genital membrane muscle, ventral 2nd valvifer-venom gland reservoir muscle, T9-genital membrane muscle) are described here for the first time in chalcidoids. The anterior and posterior 2nd valvifer-2nd valvula muscles are adapted in function. (1) In the active probing position, they enable the wasps to pull the base of each of the longitudinally split and asymmetrically overlapping halves of the 2nd valvula that are fused at the apex dorsally, thus enabling lateral bending of the terebra. Concurrently, the 1st valvulae can be pro- and retracted regardless of this bending. (2) These muscles can also rotate the 2nd valvula and therefore the whole terebra at the basal articulation, allowing bending in various directions. The position of the terebra is anchored at the puncture site in hard substrates (in which drilling is extremely energy- and time-consuming). A freely steerable terebra increases the chance of contacting a potential host within a concealed cavity. The evolution of the ability actively to steer the terebra can be considered a key innovation that has putatively contributed to the acquisition of new hosts to a parasitoid’s host range. Such shifts in host exploitation, each followed by rapid radiations, have probably aided the evolutionary success of Chalcidoidea (with more than 500,000 species estimated).